Systems Biology Reveals Relevant Gaps in Fc-γR Expression, Impaired Regulatory Cytokine Microenvironment Interfaced With Anti-Trypanosoma cruzi IgG Reactivity in Cardiac Chagas Disease Patients - Gomes, Juliana de A. S.; de Araújo, Fernanda F.; Vitelli-Avelar, Daniele M.; Sathler-Avelar, Renato; Lage, Paula S.; Wendling, Ana P. B.; do Vale, Isabela N. P. C.; Dias, João C. P.; Elói-Santos, Silvana M.; Teixeira-Carvalho, Andréa; Martins-Filho, Olindo A. (Frontiers in Microbiology, 2018)
The systems biology approach has become an innovative tool when it comes to shedding light on the complex immune response underling the development/maintenance of distinct clinical forms of Chagas disease. The goal of this study was to describe an integrative overview of Fc-gR expression, cytokine microenvironment and anti-T. cruzi IgG interface in indeterminate-(IND) and cardiac-(CARD) patients. Data demonstrated that IND displayed an overall higher Fcg-R expression (CD16; CD32; CD64) on neutrophils-(NEU), along with (CD16; CD64) on monocytes-(MON) as compared to CARD. Additionally, CARD presented an increased expression of CD32 in B-cells. While preserved frequency of IL-10-producing cells was observed in IND, decreased levels of IL-10+phagocytes and enhanced TNF+MON and NK-cells were observed in CARD. T. cruzi-antigen recall in vitro induces a general decrease of Fc-gR expression in Chagas disease patients, especially in CARD. Moreover, T. cruzi-antigen stimuli triggered a concomitant increase of IFN-g+NEU/TNF+NK-cells and IL-10+MON/IL-10+B-cells in IND. Biomarker signatures further emphasized the contrasting Fc-gR expression and cytokine microenvironment observed in Chagas disease patients with distinct clinical forms. Up-regulation of Fc-gR expression (CD16 on NEU;MON;NK) was observed in IND, whereas a general decrease was reported for CARD. Moreover, while a mixed cytokine microenvironment (TNF; IL-10) was observed in IND, CARD presented a contrasting profile with up-regulation of TNF+NEU and IL-12+NEU. Integrative network analysis revealed a distinct assemblage of biomarkers, with CARD presenting a large number of negative internode connectivity in comparison with IND. The relevant gaps in Fc-gR expression and impaired regulatory cytokine microenvironment interfaced with the anti-T. cruzi IgG reactivity throughout an exacerbated negative connectivity may account for the development/maintenance of the clinical status of cardiac Chagas disease.